Corrigendum: Genome Size Doubling Arises From the Differential Repetitive DNA Dynamics in the Genus Heloniopsis (Melanthiaceae) - Pellicer, Jaume; Fernández, Pol; Fay, Michael F; Michálková, Ester; Leitch, Ilia J (Frontiers in genetics, 2021)
[This corrects the article DOI: 10.3389/fgene.2021.726211.].
Keywords: transposable elements; C-value; DNA repeats; chromosome; satellite DNA